Redefining success in innovative crowdfunding projects: Empirical evidence of effective mindful consumption promotion in Kickstarter - Ana M. Gómez-Olmedo; María Eizaguirre Diéguez; Jose Antonio Vicente Pascual (Journal of Innovation & Knowledge)
The crowdfunding movement has created opportunities for entrepreneurs to overcome financial barriers and initiate innovative projects that can alter consumer behaviour towards more sustainable consumption practices, particularly mindful consumption. Mindful consumption involves incorporating acquisitive, repetitive and aspirational behaviours and purchasing decisions that consider the impact on ecosystems and communities. While previous research has identified success factors such as project descriptions, financing goals, social capital and innovation, their influence on crowdfunding success through the lens of mindful consumption could be less determinant. The entire concept of what success entails can also be redefined and, with it, the impact of startups. This study fills this research gap by determining the factors that contribute to the success of environmental projects in reward-based crowdfunding and understanding how such projects also promote consumers’ sustainable consumption practices. The study employs fuzzy-set qualitative comparative analysis on a sample of 210 Kickstarter projects in the environmental category to identify the necessary conditions for crowdfunding success and unravel the complex factors at play between success and mindful consumption. The results are consistent with previous literature finding that integrating monetary-related keywords alone is not enough for crowdfunding success, indicating that the overall understanding of startup success should be revisited to include social capital. Identifying the necessary conditions for redefining success also contributes to the formation of guidelines to assure sustainable innovation for new ventures in reward-based crowdfunding platforms such as Kickstarter.